Tulisan Pegon Wujud Identitas Islam-Jawa Tinjauan atas Bentuk dan Fungsinya - Pudjiastuti, Titik (SUHUF, 2009)
Islam comes to Java in 15th-16th centuries did not only introduce the religious concepts but also Arabic scripts. The impact of the penetration of Islam was the production of new civilization which is known as Islamic-Javanese civilization. The Arabic scripts which at first were taught for the sake of understanding Islamic teachings and of writing Islamic text in Arabic, were eventually developed, modified and adapted to the Javanese tongue and then can be used as the tool to write the texts in Javanese literature. This modified Arabic-Javanese script is known as pegon. The original purpose of creating pegon script was related to the mission of spreading Islam but in further development is also functioned as the medium of writing many purposes and interests such as for writing literary texts, documents, private letters, etc